Murraya Koenigii (L.) Spreng-Curry Leaves/Mitho Nim- A Miracle Plant - Singh, Anant Gopal (Butwal Campus Journal, 2020)
Murraya koenigii is a leafy medicinal as well as a green leafy aromatic shrub that belong to the family Rutaceae of angiosperms. The various pharmacological activities of the plant have been seen such as activity on Antidiabetic, cholesterol-reducing property, antimicrobial activity antiulcer activity, Antioxidative property, anti-diarrhea activity, anti-cancer activity with mucother phagocytic activity.